The Effectiveness of Animated Video in Differentiated Learning on Students’ Motivation and Arabic Learning Achievement at SMKS Al-Ikhwaniyah - Subhan Al Afghani; Hanik Mahliatussikah; Moch.Wahib dariyadi; Muhammad Sofwan bin Harizan (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2026)
This study aims to evaluate the effectiveness of animated video media within a differentiated learning framework in enhancing students’ motivation and learning outcomes in Arabic at vocational high schools. Employing a quantitative quasi-experimental design with a pretest–posttest control group, the research involved 46 eleventh-grade students at SMKS Al-Ikhwaniyah, Tangerang Selatan. The experimental group received differentiated instruction supported by animated video media, while the control group was taught using conventional methods. Data were collected using achievement tests and motivation questionnaires based on the ARCS model (Attention, Relevance, Confidence, Satisfaction) and analyzed through descriptive and inferential statistics, including independent samples t-tests. The findings reveal that students in the experimental group demonstrated significantly greater improvements in both motivation and academic performance compared to the control group, with mean posttest gains of 18.4 and 9.2 points, respectively. Statistical analysis (t = 9.394; p < 0.05) and a large effect size (Cohen’s d = 0.71) indicate a strong positive impact of the intervention. Notably, motivation increased across all ARCS dimensions, particularly in Attention and Confidence. In conclusion, the integration of animated video media into differentiated learning significantly enhances both cognitive and affective learning outcomes, suggesting its effectiveness as a pedagogical strategy for Arabic language instruction in vocational education contexts.